Multi-instrumented observations of the equatorial F-region during June solstice: large-scale wave structures and spread-F - Fabiano S. Rodrigues; Dustin A. Hickey; Weijia Zhan; Carlos R. Martinis; Bela G. Fejer; Marco A. Milla; Juan F. Arratia (Progress in Earth and Planetary Science, 2018)
Abstract Typical equatorial spread-F events are often said to occur during post-sunset, equinox conditions in most longitude sectors. Recent studies, however, have found an unexpected high occurrence of ionospheric F-region irregularities during June solstice, when conditions are believed to be unfavorable for the development of plasma instabilities responsible for equatorial spread-F (ESF). This study reports new results of a multi-instrumented investigation with the objective to better specify the occurrence of these atypical June solstice ESF in the American sector and better understand the conditions prior to their development. We present the first observations of June solstice ESF events over the Jicamarca Radio Observatory (11.95° S, 76.87° W, ∼ 1° dip latitude) made by a 14-panel version of the Advanced Modular Incoherent Scatter Radar system (AMISR-14). The observations were made between July 11 and August 4, 2016, under low solar flux conditions and in conjunction with dual-frequency GPS, airglow, and digisonde measurements. We found echoes occurring in the pre-, post-, and both pre- and post-midnight sectors. While at least some of these June solstice ESF events could have been attributed to disturbed electric fields, a few events also occurred during geomagnetically quiet conditions. The late appearance (22:00 LT or later) of three of the observed events, during clear-sky nights, provided a unique opportunity to investigate the equatorial bottomside F-region conditions, prior to ESF, using nighttime airglow measurements. We found that the airglow measurements (630 nm) made by a collocated all-sky camera show the occurrence of ionospheric bottomside F-region perturbations prior to the detection of ESF echoes in all three nights. The airglow fluctuations appear as early as 1 hour prior to radar echoes, grow in amplitude, and then coincide with ESF structures observed by AMISR-14 and GPS TEC measurements. They also show some of the features of the so-called large-scale wave structures (LSWS) that have been detected, previously, using other types of observations and have been suggested to be precursors of ESF. The bottomside fluctuations have zonal spacings between 300 and 500 km, are aligned with the magnetic meridian, and extend at least a few degrees in magnetic latitude.